POTENSI KAPANG PELAPUK PUTIH Phanerochaete chrysosporium DALAM PENGOLAHAN LIMBAH INDUSTRI TEKSTIL - Yulinah Trihadiningrum (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Phanerochaete chrysosporium was known as white rot mold which could biodegrade persistent organic pollutants. In this research the ability of the mold in biodegrading textile dye direct orange S and rhemazol yellow, which contained naphtol functional group, was studied. This research included characterization of the waste water and determination of optimum concentration of the waste water for biodegradation. The optimum concentration for biodegradation was determined by measuring the radial growth of the mold in agar medium containing various concentrations of textile dye. The final stage was the application of the mold for biodegrading the textile dye in aerobic batch reactor using the selected concentration. This research showed that P. chrysosporium could grow satisfactorily in minimum medium containing synthetic textile wastewater in various concentrations. The highest colour removal efficiency of 93% was achieved in 3 days in the waste water with highest color intensity (absorbance value l520 = 4.00), and 48% in the waste water with absorbance value l520 = 1.22. COD removal efficiency of 87% was achieved within 12 days in the wastewater of 30% concentration, and 83% in the waste water of 100% concentration. The pH values decreased to 3.23 in the waste water with lower dye concentration and to 3.42 in the higher color intensity, from the initial values of 5.0-6.0. This research concluded that P. chrysosporium was capable to biodegrade naphtol textile dye with reasonably high efficiency.